Low-Dose Gamma Knife Radiosurgery for Acromegaly. Issue 1 (29th August 2018) - Pai, Fu-Yuan; Chen, Ching-Jen; Wang, Wen-Hsin; Yang, Huai-Che; Lin, Chung Jung; Wu, Hsiu-Mei; Lin, Yi-Chun; Chen, Harn-Shen; Yen, Yu-Shu; Chung, Wen-Yuh; Guo, Wan-Yuo; Pan, David Hung-Chi; et al.
Abstract: Background: Remission rate is associated with higher dose of Gamma Knife Radiosurgery (GKRS; Gamma Knife: Elekta AB, Stockholm, Sweden) for acromegaly, but the dose ≥25 Gy is not always feasible when the functioning adenoma is close to optic apparatus Objective: To evaluate the efficacy and safety of low-dose (<25 Gy) GKRS in the treatment of patients with acromegaly. Methods: Single-center retrospective review of acromegaly cases treated with GKRS between June 1994 and December 2016. A total of 76 patients with the diagnosis of acromegaly who were treated with low-dose GKRS were selected for inclusion. Patients were treated with a median margin dose, isodose line, and treatment volume of 15.8 Gy, 57.5%, and 4.8 mL, respectively. Any identifiable portion of the optic apparatus was limited to a radiation dose of 10 Gy. All patients underwent full endocrine, ophthalmological, and imaging evaluation prior to and after GKRS treatments, and results of these were analyzed. Results: Biochemical remission was achieved in 33 (43.4%) patients. Actuarial remission rates were 20.3%, 49.9%, and 76.3% at 4, 8, and 12 yr, respectively. Absence of cavernous sinus invasion ( P  = .042) and lower baseline insulin-like growth factor-1 levels ( P  = .019) were significant predictors of remission. New hormone deficiencies were found in 9 (11.8%) patients. Actuarial hormone deficiency rates were 3%, 14%, and 22.2% at 4, 8, and 10 yr, respectively. Two (2.6%) patients who achieved initial remission experienced recurrence. No optic complications were encountered. CONCLUSION: Reasonable remission and new hormone deficiency rates can be achieved with low-dose GKRS for acromegaly. These rates may be comparable to those with standard GKRS margin doses.